A randomized controlled trial of a brief self-compassion intervention designed to improve the body image of sexual minority men. (September 2022) - Grey, Wesley; Harris, Emily A.; Griffiths, Scott
Abstract: Self-compassion involves reflecting on shared human experiences, expressing self-kindness, and responding to feelings in a kind and non-judgmental way. Self-compassion interventions seem to be effective for women's body dissatisfaction, however, such interventions have not been trialed with men, including sexual minority men, who are particularly vulnerable. We conducted a randomized controlled trial of a brief self-compassion intervention designed to reduce body dissatisfaction among sexual minority men ( N = 605). We used a 3 (condition: self-compassion, self-esteem, and a benign recollection control) × 5 (time) repeated measures design, whereby participants completed a brief writing task and completed body image measures at multiple time-points. Participants in both the self-compassion and self-esteem conditions showed improved body image and self-compassion following the intervention whereas participants in the control condition did not. Increases in self-compassion mediated body image measures for participants in the self-compassion but not self-esteem or control conditions. Participants in the self-compassion condition also showed increased self-compassion at three-weeks follow-up. While several caveats to our results were noted, our overall interpretation is that self-compassion and self-esteem interventions might be effective for sexual minority men's body image, and more research is necessary. The challenge of inculcating a self-compassionate mindset among men is also discussed. Highlights: Self-compassion improves body image in sexual minority men. Self-compassion does not outperform self-esteem as a body image intervention. Self-compassionate writing improves body image via self-compassion. Self-compassionate writing improves self-compassion at three-weeks follow-up. Self-compassionate writing attenuates the effects of upward appearance comparisons.